« Is that wool hat my hat ? » - Hélène Aji (Transatlantica)
Do poems give us something to « see » ? Contemporary American poems, from Ezra Pound’s Imagist poems and William Carlos Williams’s poems as objects, gradually reform the poem into a space dedicated to conceptualization (George Open, Robert Duncan) or evidencing the very alienation lurking in the commitment to concepts as opposed to praxis (Jackson Mac Low). As poets aspire to a visual poem, opt for abstraction or radically decide to suppress the representational from the poem, images, as raw material for the poetic or as vehicles for meaning, are replaced with structures that question our modes of apprehending language and the discourses that constitute our modes of being in language.